Disaster hypertension and cardiovascular events in disaster and COVID‐19 pandemic. Issue 3 (1st February 2021) - Narita, Keisuke; Hoshide, Satoshi; Tsoi, Kelvin; Siddique, Saulat; Shin, Jinho; Chia, Yook‐Chin; Tay, Jam Chin; Teo, Boon Wee; Turana, Yuda; Chen, Chen‐Huan; Cheng, Hao‐Min; Sogunuru, Guru Prasad; et al.
Abstract: The incidence of large disasters has been increasing worldwide. This has led to a growing interest in disaster medicine. In this review, we report current evidence related to disasters and coronavirus disease‐2019 (COVID‐19) pandemic, such as cardiovascular diseases during disasters, management of disaster hypertension, and cardiovascular diseases associated with COVID‐19. This review summarizes the time course and mechanisms of disaster‐related diseases. It also discusses the use of information and communication technology (ICT) as a cardiovascular risk management strategy to prevent cardiovascular events. During the 2011 Great East Japan Earthquake, we used the "Disaster Cardiovascular Prevention" system that was employed for blood pressure (BP) monitoring and risk management using ICT. We introduced an ICT‐based BP monitoring device at evacuation centers and shared patients' BP values in the database to support BP management by remote monitoring, which led to improved BP control. Effective use of telemedicine using ICT is important for risk management of cardiovascular diseases during disasters and pandemics in the future.